Selected stories of O. Henry - Henry, O., 1862-1910 (Barnes & Noble classics., 2003)
O. Henry--master of the one-line quip and surprise ending, and reinventor of the short story--today enjoys greater popularity than ever. His descriptions of New York City and the American West have become ingrained into the fabric of modern American psychology. His character sketches--always humorous, always sympathetic, and always a little melancholy--remind us that life must be lived evenly, with pluck and perseverance. This special edition features commentaries, legacies, and discussion questions. Victoria Blake has worked at The Paris Review and contributed to The Boulder Daily Camera, a number of small literary presses in the United States, and several English-language publications in Bangkok, Thailand. She wrote the introduction and notes to the Barnes & Noble Classics edition of D.H. Lawrence's "Sons and Lovers. She currently lives and works in San Diego, California.